{(S)-2-[({2-[1-(Anthracen-9-ylmethyl)-pyrrolidine-2-carboxamido]phenyl}-(phenyl)methylidene)amino]acetato(2)-kappa4N,N´,N´´,O1}nickel(II) - Padělková, Zdeňka; Popkov, Alexander; Nádvorník, Milan (International Union of Crystallography, 2012)
The title compound, [Ni(C 35H 29N 3O 3)], includes a Schiff base ligand derived from (S)-1-[(anthracen-9- yl)methyl]-N-(2-benzoylphenyl)pyrrolidine-2-carboxamide and glycine. The Ni II atom is coordinated by three N atoms [Ni - N = 1.937 (3), 1.850 (3) and 1.850 (3) Å] and one O atom [Ni - O = 1.859 (2) Å], resulting in a pseudo-square-planar coordination environment.
{(S)-2-[({2-[1-(Anthracen-9-ylmethyl)-pyrrolidin-2-carboxamido]phenyl}-(phenyl)methylidene)amino]acetato(2)-kappa4N,N´´,N´´,O1}nikelnatý komplex
Keywords: chiral nickel-complex; alpha-amino-acids; C-13 NMR-spectra; schiff-base; asymmetric-synthesis; x-ray; glycine; chirální nikelnatý komplex; alfa-aminokyseliny; C-13 NMR-spektra; Schiffovy báze; asymmetrická syntéza; rentgenostrukturální analýza; glycin